Deep phenotyping through biomarker profiling of frontotemporal dementia (FTD) with and without co-morbid motor neuron degeneration: A multidimensional approach - Omer, Taha (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2018)
PhD Thesis abstract: Trinity College Dublin Title: Deep Phenotyping Through biomarker Profiling of Frontotemporal Dementia (FTD) With and Without Co-morbid Motor Neuron Degeneration: A Multidimensional Approach Authors: Student: Taha Adam Omer 12328449 Supervisor: Orla Hardiman The overall objective of this thesis, which is based on the central theme of biomarkers and progression in Neurodegeneration, was to perform deep phenotyping of Frontotemporal Dementia (FTD) and related disorders of motor neuron degeneration through multimodal biomarker profiling. Incorporated into the deep phenotyping are clinical characterization, neurophysiological assessment, family aggregation analysis, genetics, imaging and outcome. This project exploits a clinic-based, case control design integrating interconnected complementary cross-sectional and longitudinal approaches. Results from the neurophysiology arm of this thesis included utilizing MUNIX to establish lower motor neuron repository, to study disease progression and to quantify lower motor neuron dysfunction in FTD. The aggregation of neuropsychiatric and neurodegenerative diseases including schizophrenia, suicide, learning disability and Motor Neuron Disease were also elevated in relatives of FTD patients compared to relatives of controls. A separate chapter in this thesis described the experience of our cognitive clinic over the study period. The multiparametric comparative Magnetic Resonance Imaging study described grey and white matter patterns across the FTD-ALS spectrum including the finding that FTD-ALS patients who tested negative for hexanucleotide repeats in C9orf72 had considerable extra-motor frontotemporal pathology, which is more prominent than that observed in C9orf72 positive patients. Overall the biomarkers generated from this research are likely to represent valuable markers in future discovering of distinct disease subtypes within the FTD-ALS spectrum. In the final section, results generated from this research are used to propose future research projects and key findings of this thesis are expected to have significant implications on both clinical care and future research in the field of Frontotemporal dementia.
APPROVED
Keywords: Frontotemporal Dementia (FTD); Phenotyping; Motor Neurone Degeneration; Biomarkers